Community Empowerment through Appropriate Technology and Business Feasibility Analysis of Melinjo-Based Processed Products in Ulim District, Pidie Jaya Regency - Dewi Sri Jayanti; Teuku Ferijal; Hendri Syah; Raida Agustina; Siti Mechram; Diana Sapha AH (Jurnal Pengabdian Bakti Akademisi, 2026)
Melinjo is a local commodity with strong potential to be developed into a range of value-added processed products, yet its utilization is still largely limited to raw materials or simple processing, resulting in low economic value. This community service program aimed to improve the capacity of local communities in Ulim District, Pidie Jaya Regency, to process melinjo into marketable products through the introduction of appropriate processing technology, practical training, and business feasibility analysis. The program was implemented using a participatory approach consisting of preparation, community education, demonstration, hands-on practice, mentoring, and evaluation. The technologies introduced included a roasting machine, an emping flattening device, a dryer, a flour milling machine, and a sealer. The results showed that participants were able to produce several melinjo-based products, including emping melinjo, melinjo flour, sweet and spicy emping melinjo, melinjo kastengel, crispy melinjo cookies, and candied melinjo peel. Evaluation results also indicated a very positive response from the community toward the program. Business feasibility analysis demonstrated that all products generated positive profits, with revenue-cost ratios greater than one and benefit-cost ratios greater than zero, while both selling prices and production volumes exceeded the break-even point. These findings indicate that melinjo-based processed products are economically feasible and profitable. Overall, the program not only improved community knowledge and technical skills but also showed that the diversification of melinjo products has strong potential to support household-scale and small-scale enterprises based on local resources.